2019
DOI: 10.1002/anie.201813999
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Strategy for the Construction of Covalent Organic Frameworks from Nonporous Covalent Organic Polymers

Abstract: The field of covalent organic frameworks (COFs) has been developed significantly in the past decade on account of their important characteristics and vast application potential. On the other hand, the discovery of novel synthetic methodology is still ac hallenging task to further promote the preparation of COFs.H erein, an interesting protocol for the conversion of amorphous nonporous covalent organic polymers (COPs) to COFs was established, affording four COFs with high crystallinity and porosity.S pecificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 53 publications
0
59
0
Order By: Relevance
“…[16] However, the final few-layered h-BNNS obtained through these approaches often suffer from low surface areas or amorphous/low crystalline structures. [21] Herein, an ovel strategy was developed for the successful transformation of amorphous bulk h-BN to h-BNNS with high crystallinity and porosity,w hich was fully characterized by powder X-ray diffraction (PXRD), microscopy and N 2 adsorption/desorption isotherms.T he essence of this strategy lies in the successive dissolution-precipitation/crystallization of amorphous h-BN precursor in the presence of magnesium ( Figure 1A). [20] In addition, the high crystallinity makes their structures easier to be determined by using powder X-ray diffraction (PXRD) and high-resolution transmission electron microscopy (HR-TEM).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[16] However, the final few-layered h-BNNS obtained through these approaches often suffer from low surface areas or amorphous/low crystalline structures. [21] Herein, an ovel strategy was developed for the successful transformation of amorphous bulk h-BN to h-BNNS with high crystallinity and porosity,w hich was fully characterized by powder X-ray diffraction (PXRD), microscopy and N 2 adsorption/desorption isotherms.T he essence of this strategy lies in the successive dissolution-precipitation/crystallization of amorphous h-BN precursor in the presence of magnesium ( Figure 1A). [20] In addition, the high crystallinity makes their structures easier to be determined by using powder X-ray diffraction (PXRD) and high-resolution transmission electron microscopy (HR-TEM).…”
mentioning
confidence: 99%
“…Recently,t his protocol was utilized in the conversion of amorphous covalent organic polymers (COPs) to COFs of high crystallinity and porosity by replacing the linkers. [21] Herein, an ovel strategy was developed for the successful transformation of amorphous bulk h-BN to h-BNNS with high crystallinity and porosity,w hich was fully characterized by powder X-ray diffraction (PXRD), microscopy and N 2 adsorption/desorption isotherms.T he essence of this strategy lies in the successive dissolution-precipitation/crystallization of amorphous h-BN precursor in the presence of magnesium ( Figure 1A). Thep roduced crystalline h-BNNS consisted primarily of thin layers in ah igh mass yield of 88 %.…”
mentioning
confidence: 99%
“…ForC OF-3, the value is similar to the material synthesized by the direct approach (1700 m 2 g À1 ), [16] while the value for COF-4 is much higher than that synthesized by the direct method (2238 m 2 g À1 )a nd the COP-to-COF strategy (2143 m 2 g À1 ). [12,17] All these results demonstrated that the linkage replacement from polyimide-based COP-2 to iminebased COF-3 and COF-4 was very successful.…”
Section: Angewandte Chemiementioning
confidence: 87%
“…We thus developed aC OP-to-COF conversion strategy to obtain COFs with high crystallinity and porosity. [12] Current reports on the linker substitution during the construction of COFs are limited to the same type of linkages with the same type of reactions. There is still no report of the linkage substitution using different types of linkages under different types of reactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation